Holding on in Moments of Not Knowing: Disequilibrium, Reflective Judgment, and Practicing Adaptive Leadership. Issue 168 (30th November 2020) - McLaughlin, Conor P.
Abstract: In this chapter, the author discusses the role of disequilibrium in leadership development and provides tangible examples of ways to employ theories in designing intentional moments of disequilibrium.